2018
DOI: 10.1080/15622975.2018.1468030
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytics targeting GABAA receptors: Insights on etifoxine

Abstract: Novel therapeutic strategies have been emerging following the recognition of neurosteroids as potent anxiolytics. Featured at the top of the list for well-tolerated anxiety relief, TSPO ligands such as etifoxine appear promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 82 publications
0
21
0
Order By: Relevance
“…GABA A receptors in the central nervous system are known as the major targets for the first line treatment of anxiety ( Poisbeau et al, 2018 ). GABA A receptors subunits, mainly including GABRA1, GABRA2, and GABRA3, have been reported to mediates anxiolysis ( Möhler, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA A receptors in the central nervous system are known as the major targets for the first line treatment of anxiety ( Poisbeau et al, 2018 ). GABA A receptors subunits, mainly including GABRA1, GABRA2, and GABRA3, have been reported to mediates anxiolysis ( Möhler, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these findings suggest that SZJ extract mainly exerts an anxiolytic effect via modulation of serotonergic and GABAergic systems. GABA A receptors in the central nervous system are known as the major targets for the first line treatment of anxiety (Poisbeau et al, 2018). GABA A receptors subunits, mainly including GABRA1, GABRA2, and GABRA3, have been reported to mediates anxiolysis (Möhler, 2012).…”
Section: Go and Kegg Pathway Enrichment And Analysismentioning
confidence: 99%
“…In the present study, TSPO ligands (XBD173, 25 µM and Etifoxine, 20 µM) enhanced cholesterol efflux and upregulated expression of cholesterol-efflux-related genes in choroidal endothelial cells (Figure 1C and Figure 2). Our previous work also used Etifoxine and XBD173 at same concentration to treat RPE cells and found the effect of both ligands on cholesterol efflux was TSPO-dependent [22], though early reports suggested Etifoxine also binds to GABA A Rs on β subunits [44]. Interesting Costa et al recently reported that the neurosteroidogenic ability of both Etifoxine and XBD173 is dependent on residence time at the binding site rather than their binding affinities [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…However, the first choice of pharmacological treatment for anxiety disorders consists in benzodiazepines, in spite of the risk of dependence if taken over a long period of time. The mechanism of action of benzodiazepines involves the hyperpolarization of neurons, which is achieved by potentiating the action of γ-aminobutyric acid (GABA) on the ligand-gated chloride channels GABA A [ 30 ]. With GABA as the main inhibitory neurotransmitter in the central nervous system, benzodiazepine action decreases the firing of action potentials counteracting the neuronal hyperexcitability classically associated with anxiety [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of benzodiazepines involves the hyperpolarization of neurons, which is achieved by potentiating the action of γ-aminobutyric acid (GABA) on the ligand-gated chloride channels GABA A [ 30 ]. With GABA as the main inhibitory neurotransmitter in the central nervous system, benzodiazepine action decreases the firing of action potentials counteracting the neuronal hyperexcitability classically associated with anxiety [ 30 ]. In conclusion, despite strong evidence supporting models that include a dysregulation of monoaminergic, glutamatergic, and HPA systems, which are not mutually exclusive, a compelling and unified description of the neurobiology of affective disorders and the mechanisms of action of the medicines used to treat them are still unavailable.…”
Section: Introductionmentioning
confidence: 99%